Root canal configuration of human permanent mandibular first molars of an indo-dravidian population based in Southern India: An In vitro study - J V Karunakaran; Leo Sujith Samuel; Yousef Rishal; M Derick Joseph; K Rahul Suresh; Sam T Varghese (Wolters Kluwer Medknow Publications, 2017)
Aim: This study aims to analyze root canal configuration of human permanent mandibular first molars of an indo-Dravidian population based in southern India. Materials and Methods: A total of 1147 mandibular first permanent molars were collected, cleansed, and stored. The number of roots was recorded, access preparations made, pattern of orifices recorded after pulpal floor debridement, dye injected into the canals using apical negative pressure and subjected to a clearing technique. They were then analyzed using a stereo microscope and the canal configurations recorded (Vertucci). The number of roots, the pattern of orifices and canal configuration were recorded. Results: The pattern of orifices was triangular (87.9%), rectangular (8.5%), C-shaped (3.0%), and two orifice pattern (0.6%). About 95.6% of teeth had two roots, and 4.4% had three roots. The most common canal system configuration in mesial root was Vertucci type IV (52.3%), followed by type II (35%). Root canal configuration of the distal root revealed type I configuration in 62.7%, followed by types II (14.5%) and IV (12.4%). The distolingual root had a type I configuration. Conclusion: Awareness of canal configuration, adequate clinical skills, use of specialized techniques of diagnosis, debridement and obturation will pave the way for successful treatment outcomes.